Vegetation coverage variation in relation to urbanization process in Vietnam; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 336, № 3 - Hoang Phan Hai Yen (2025, 2025)
Relevance. The phenomenon of urbanization, driven by the socio-economic development requirements in various regions globally, is increasingly contributing to reductions in vegetation cover and intensifying ecological and environmental complexities. As a result, monitoring urban expansion has become indispensable for enhancing efficient urban management and facilitating planning regarding ecological and environmental issues. Aim. To assess the spatial-temporal variations in vegetation cover in Thai Nguyen City, Vietnam over the past two decades under the impacts of urbanization. Methods. The spatial-temporal changes in vegetation cover were analyzed using the maximum value composite algorithm integrated into the Google Earth Engine platform. The accuracy assessment of the applied classification method yielded high accuracy levels ranging from 91 to 94%. Results. For 2001–2023, the urban land area increased by 4024 hectares, with an average annual growth rate of 0.78%, rising from 386 hectares in 2001 to 4.410 hectares in 2023. The findings indicate a slight decrease of approximately 773 hectares in vegetation cover during 2001–2010 but a significant increase of up to 2696 hectares during 2010–2023. These findings highlight the potential risks associated with increasing urban land areas within the study area and emphasize the urgent need for appropriate measures to address this issue